Literature review the theory of planned behavior in the decision to buy organic product (National Administration Journal, 2021)
Nowadays responsible consumption towards the environment and health, modify the intention to buy, which is widely analyzed in planned behavior theory (PBT). . This article bibliographically reviews the application of PBT , by following the consultationmethodology of published scientific articles focused on determining the intention to purchase organic products. There are several studies focused on analyzing environmental concern, the behavior towards environmental sustainability, healthy habits, the environmental benefits of organic products and the consumer’s confidence towards these types of products. There is evidence that PBT allows to determine intentions and behaviors to purchase, which can be influenced by cultural and social characteristics of individuals, knowledge and environmental concern
Keywords: Behavior to purchase; intention to purchase; attitude; subjective norms; perceived control.